Edukasi Demokrasi sebagai Strategi Penanaman Bela Negara dan Pembentukan Identitas Generasi Muda: Penelitian - Joselyn Tiofanny; Angelika, Fransiska; Indriani; Tatiana, Natiella Diva; Angelita, Simthia; Dariyo, Agoes (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article aims to describe the implementation of democracy education as a strategy for instilling the values of national defense while simultaneously shaping the identity of young generations. The background of this study lies in the importance of fostering youth awareness of national values, which not only encompass formal aspects of citizenship but also critical consciousness of their role within a democratic society. The method employed was the organization of an educational seminar for high school students in West Jakarta as a form of Community Service (PKM) activity. The seminar content focused on the interconnection between democracy, national defense, and youth identity, using an interactive approach to encourage active participation from the participants. The results indicated that students demonstrated strong interest in issues related to democracy and national defense and were able to relate them to their identity as the nation’s future generation. Post-seminar evaluations revealed an increase in participants’ understanding of democracy as a foundation for strengthening national defense, as well as the emergence of critical reflections on their role in safeguarding unity, diversity, and national identity. Therefore, democracy education through seminars can be considered an effective strategy for instilling the spirit of national defense and strengthening the identity formation of young generations.